Emotion in the library workplace - Hines, Samantha (Samantha Schmehl); Matteson, Miriam L. (Emerald Publishing Limited, 2017)
Emotions are prevalent in the library workplace leading to many questions and areas of analysis worth exploring. For example, what tools for developing emotional intelligence are used effectively in library workplaces? How can emotional labor be managed to minimize the negative effects of emotion work? How can library employees express authentic emotions while still adhering to service expectations? How does dispositional affect how one experiences emotions - influence relationships in the workplace? What role does emotion play in effective as well as ideal library leadership and management? In this volume, we consider how emotions or related concepts such as affect, mood, or discrete feelings intersect with library administration. Offering eleven chapters ranging through inward reflection to outward practice, fourteen authors explore how theory has been applied in the study of emotion in the library workplace and provide a look at future trends in the area. Library managers will take away increased knowledge about how the library workplace can and should operate with consideration toward emotion, and will glean ideas for implementation with their own staff and services.
Prelims -- A primer on emotions in the workplace -- The potential of mindfulness in managing emotions in libraries -- Associations between affect, personality, and job satisfaction among library employees: efficient and ethical assessment of library staff -- Constructing authority in professional practice: personal reflections -- Avoiding burnout -- Into the weeds: emotions and deselection in the library -- Emotional intelligence: a framework for the competencies and traits of reference and user services librarians -- Legacy practices: implications for leadership -- Using civility in the form of mindful speech and action to cultivate empathy among library employees -- Let's talk about how we talk: communication agreements in the library workplace -- The role of intentional reflective practice and mindfulness in emotional self-regulation for library administrators -- Afterword -- About the Authors.
Includes index.
Includes bibliographical references.
Print version record
Keywords: Library administration; Emotions -- Sociological aspects; Psychology, Emotions; Psychology: emotions